Assessing Mortality Risk in Fournier's Gangrene: A Study Using the Simplified Prognostic Scoring System - Piyarali, Shireen; Jabeen, Mehnaz; Kumar, Sanjeet; Syed Rabiullah,; Jafri, Abbas; Akhter, Hamza; Gazder, Tanzeel; Shahzad, Asad (Indus Journal of Bioscience Research, 2024)
Background: Fournier’s gangrene (FG) is an uncommon yet serious type of necrotising fasciitis that impacts the perineal, genital, and perianal areas. The simplified prognostic scoring system for Fournier’s gangrene emphasizes essential clinical indicators, including age, body mass index (BMI), comorbidity status, and presentation timing, to develop a practical tool that facilitates rapid decision-making. Objective: To study the Risk factors for mortality using Simplified Prognostic Scoring System in patients with Fournier's gangrene. Method: A prospective study utilised a non-probability consecutive sampling technique. This investigation took place within the urology department of the Sindh Institute of Urology and Transplantation from January 2018 to June 2022. All patients admitted with the working diagnosis of Fournier’s gangrene through emergency services, from January 2018 to June 2022. Demographic information (age, gender, co-morbidities), vital signs, presentation (mode of onset), and primary body areas affected were noted. All these patients will receive conservative management, which encompasses broad-spectrum antibiotics, nutritional management, and nursing care. Additionally, each will receive debridement, and their wounds will be evaluated on a daily basis. Result: A total of 130 patients were discharged without any reported deaths from early presentations. In contrast, 183 patients were discharged, with 9 deaths noted from delayed presentations. Additionally, 2 individuals were discharged, while 17 patients succumbed during treatment due to late presentations with septic shock. Conclusion: The simplified prognostic scoring system is a valuable tool for risk stratification in patients with Fournier’s gangrene and should be routinely used in clinical practice to improve patient outcomes.